Vaccine Literacy and Hesitancy on routine and travelers’ vaccines: a preliminary online survey - Biasio, Luigi Lorenzo; Lorini, Chiara; Pecorelli, Sergio (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The vast amount of conflicting information during the COVID-19 pandemic might have had a detrimental effect on people’s opinions about vaccinations, including groups like travelers. This study aimed at assessing Vaccine Literacy in a sample of the general Italian population, together with antecedents of Vaccine Hesitancy, such as confidence, complacency, and convenience, the so-called “3Cs”, and their effects on accepting routine and travelers’ vaccines. Study Design. A specifically designed anonymous questionnaire was created by using Google forms and validated through a face validity process. Subsequently, it was employed in an online cross-sectional survey. Methods. The assessment Vaccine Literacy scale used in this survey was similar to that employed in earlier surveys. In addition to demographic data and information sources used by participants, the questionnaire was composed, in total, of nine multiple choice questions on Vaccine Literacy, and six questions on the 3Cs. Considered outcomes were self-reported participants’ beliefs, attitudes, behaviors and intentions toward recommended routinary adulthoods vaccines and arboviral vaccines for travelers. A section of the questionnaire focused on chikungunya awareness, taken as an example of arboviral disease that has caused outbreaks in Italy, but not yet vaccine-preventable at the time of the investigation. Results. After cleaning the database, 357 responses were suitable for analysis. Vaccine Literacy mean functional score was 2.81 ± 0.74 (lower than in an earlier survey, p = 0.012), while the interactive-critical (score 3.41 ± 0.50) was higher (p